Topics of articles by A. V. Kartashev in the newspaper Strana (1906‒1907) in the light of the agenda of the movement of religious intelligentsia for a church reform - Irina Vorontsova (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
In 1906‒1907, due to his articles with severe criticism of the Russian Orthodox Church, A. V. Kartashev became one of the leaders of the movement for a radical church reform in Russia. This paper raises the question about how it came to be possible that Kartashev accepted the doctine of “Neochristianity” about the “sanctity of flesh” and supported it for more than ten years. The range of topics of the articles of 1906‒1907 in the newspaper Strana refl ected a stage of Kartashev’s personal evolution from “apprenticeship” in “Neochristianity” to independent conclusions as to the accents of the church reform that the country needs after implementing constitutional reforms. Based on the material of Kartashev’s essayism of 1906‒1907 and conceptual formulae of the “new religious consciousness”, this paper shows that during these years Kartashev denied the possibility of renovation of the Russian church in many respects, nevertheles combining his criticism with love for Christianity and belief in its social prospects. The paper also sheds light on Kartashev’s relations with representatives of the “left wing” in the movement for church reform and the reason for latter being criticised by “Neochristians”.